EVALUASI JIWA KEPEMIMPINAN SANTRI DITINJAU DARI KEPEMIMPINAN KENABIAN - Redha Al Azmi; TA. Prapancha Hary (Universitas Sarjanawiyata Tamansiswa, 2013)
Â ABSTRACTThis study aimed to describe the evaluation of leadership skills of students in terms of the prophetic leadership. in addition, this study aimed to analyzethe problem in evaluating leadership qualities of students.Subjects in this study were active students at boarding school Raudhatul Muttaqien (PPRM) St. Cangkringan KM 14 Babadan Purwomartani Kalasan, Sleman, Yogyakarta academic year 2014/2015. These students attending Madrasah Tsyanawiah and Madrasah Aliyah Raudhatul Muttaqien, aged 12-18 years and active in the organization. This study uses data collection techniques using interviews and observations.Results ofstudies have provided an understanding that the process of learning the prophetic leadership students do not stop at the time at PPRM course, but the processs will continue until the end of life. In general, it is known that the learning process prophetic leadership has been going well, althoughthere areconstraints thatare found but it is not a significant problem.Keynote: Leadership Skills, Students , Prophetic LeadershipÂ